Serving the Public as Civil Servants or Citizens? Public Employees’ Exposure to Public Participation, Job Satisfaction, and Volunteering - Tipeng Chen (Review of Public Personnel Administration, 2026)
Public employees serve the public interest through their work and extend this commitment through volunteerism. However, it remains unclear what motivates them to volunteer when professional roles already fulfill intrinsic prosocial motivations. Drawing on theories from multiple life domains and public service motivation, this study examines how public sector workplace experiences, specifically exposure to public participation and job satisfaction, are associated with volunteering behavior. Using cross-sectional, nationally representative survey data from U.S. local government managers, this study finds that the relationships vary by individuals’ prior volunteering status. Among non-volunteers, higher levels of public participation exposure and job satisfaction are both associated with a greater probability of initiating volunteering. Among current volunteers, lower levels are associated with greater time devoted to volunteering, whereas higher levels are linked to volunteering across a wider range of domains. Job satisfaction negatively moderates the relationship between public participation exposure and volunteering intensity. This study extends conventional understanding of public employee volunteering beyond public service motivation and sector differences by demonstrating a contingent work–volunteerism association, offering practical insights into managing workplace experiences to sustain public service both within and beyond organizational boundaries.